DAMPAK SOSIAL EKONOMI PERKEBUNAN KELAPA SAWIT TERHADAP MASYARAKAT PEDESAAN DI DESA NANGA PALIKODAN KABUPATEN LAMANDAU - IHDA ANDREY YANUAR SETIAWAN; Nur ikhsan; Yulio Kristian Tinduh; Tesia Yiska (Innofarm : Jurnal Inovasi Petanian, 2026)
This study aims to analyze the impact of oil palm plantations on the socio-economic conditions of communities in Nanga Palikodan Village, Lamandau Regency. The research employed a quantitative approach using a survey method involving 38 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using a Likert scale to compare community conditions before and after the establishment of oil palm plantations. The results indicate that oil palm plantations have a positive impact on the community, as reflected in increased income and improved housing conditions. In addition, improvements were observed in road access, electricity, and village infrastructure such as educational facilities and places of worship. These developments are also supported by the creation of employment opportunities for local communities and increased sales of Fresh Fruit Bunches (FFB) as a major source of income. The price of FFB also contributes to improving household income. Furthermore, oil palm plantation companies contribute socially through Corporate Social Responsibility (CSR) programs, including support for the development and improvement of public facilities in the village. Therefore, oil palm plantations play an important role in improving community welfare and supporting rural development in Nanga Palikodan Village. Keywords:oil palm plantation; socio-economic impact; community income; rural infrastructure; Nanga Polikodan Village